2013
DOI: 10.1002/14651858.cd000452.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Support for mothers, fathers and families after perinatal death

Abstract: Background Provision of an empathetic, sensitive, caring environment and strategies to support mothers, fathers and their families experiencing perinatal death are now an accepted part of maternity services in many countries. Interventions such as psychological support or counselling, or both, have been suggested to improve outcomes for parents and families a er perinatal death. Objectives To assess the e ect of any form of intervention (i.e. medical, nursing, midwifery, social work, psychology, counselling or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
123
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 102 publications
5
123
0
7
Order By: Relevance
“…Hence, it is essential to offer and make accessible to pregnant women appropriate support from caregivers and their direct social networks. This helps to overcome the psychological crisis and moderates the psychological trauma (Koopmans, Wilson, Cacciatore, & Flenady, 2013). To date, various studies have explored the social field of perinatal loss, leading to the widespread development and implementation of a range of support interventions, including perinatal palliative care, birthing options after diagnosis of foetal death, pain relief and sedation, seeing and holding the dead baby, memory creation, Web-based support, culturally sensitive care, counselling, psychotherapy, and other approaches (Endo, Yonemoto, & Yamada, 2015;Koopmans et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is essential to offer and make accessible to pregnant women appropriate support from caregivers and their direct social networks. This helps to overcome the psychological crisis and moderates the psychological trauma (Koopmans, Wilson, Cacciatore, & Flenady, 2013). To date, various studies have explored the social field of perinatal loss, leading to the widespread development and implementation of a range of support interventions, including perinatal palliative care, birthing options after diagnosis of foetal death, pain relief and sedation, seeing and holding the dead baby, memory creation, Web-based support, culturally sensitive care, counselling, psychotherapy, and other approaches (Endo, Yonemoto, & Yamada, 2015;Koopmans et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(9-14.) Tuen merkitys lapsen kuoleman jälkeisessä tilanteessa on tunnistettu, ja tutkimusta erilaisista tukimuo doista ja niiden vaikuttavuudesta on tehty (13,(15)(16)(17)(18)(19). Myös parisuhdenäkökulma on ollut kes kiössä joissakin tutkimuksissa (3,(6)(7)(8)(20)(21)(22), mutta parisuhteeseen toivottua tukea lapsen kuoleman jälkeisessä elämäntilanteessa ei ole tutkittu, vaikka tiedetään lapsen kuoleman ole van kriisi parisuhteelle (3,6,7).…”
Section: A R T I K K E L Iunclassified
“…Teoreettisena lähtökohtana toimivat ymmär rys lapsen kuolemasta parisuhteeseen vaikut tavana tekijänä ja näkemys tuen tärkeydestä lapsen kuoleman jälkeisessä elämäntilanteessa (9)(10)(11)(12)(13)(14)18).…”
Section: A R T I K K E L Iunclassified
“…However, there are no studies pertaining to the experiences of post-traumatic growth in mothers whose baby died in the neonatal period. A recent Cochrane review identified a need for further research into the area of perinatal death and post-traumatic growth, in order to develop more effective post-loss interventions (Koopmans, Wilson, Cacciatore, & Flenady, 2013). A qualitative method is best suited to explore the complex experiences of mothers whose neonatal baby has died.…”
Section: Introductionmentioning
confidence: 99%